2016
DOI: 10.1111/jphp.12499
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal tails of 4,4'-diphenylmethane-bis(methyl) carbamate are essential for binding to receptor for advanced glycation end products to attenuate advanced glycation end products-induced inflammation and apoptosis responses in human umbilical vein endothelial cells

Abstract: Our findings suggested that the C-terminal tails (methoxycarbonyl groups) of CM1 were the active groups for binding to RAGE and then led to the attenuation on RAGE-mediated endothelial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Meanwhile, posttranscriptional regulation by microRNAs, such as miR200b, miR200c, and miR214, also contributes to apoptosis [ 32 , 33 ]. Incubation with AGEs may increase RAGE expression and expand the damaging effects of AGEs [ 8 ]. Taken together, previous studies and ours indicated that AGEs could induce apoptosis in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, posttranscriptional regulation by microRNAs, such as miR200b, miR200c, and miR214, also contributes to apoptosis [ 32 , 33 ]. Incubation with AGEs may increase RAGE expression and expand the damaging effects of AGEs [ 8 ]. Taken together, previous studies and ours indicated that AGEs could induce apoptosis in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%